Microparticles, Microspheres, and Microcapsules for Advanced Drug Delivery - Miléna Lengyel; Nikolett Kállai-Szabó; Vince Antal; András József Laki; István Antal (MDPI AG, 2019)
Microparticles, microspheres, and microcapsules are widely used constituents of multiparticulate drug delivery systems, offering both therapeutic and technological advantages. Microparticles are generally in the 1−1000 µm size range, serve as multiunit drug delivery systems with well-defined physiological and pharmacokinetic benefits in order to improve the effectiveness, tolerability, and patient compliance. This paper reviews their evolution, significance, and formulation factors (excipients and procedures), as well as their most important practical applications (inhaled insulin, liposomal preparations). The article presents the most important structures of microparticles (microspheres, microcapsules, coated pellets, etc.), interpreted with microscopic images too. The most significant production processes (spray drying, extrusion, coacervation, freeze-drying, microfluidics), the drug release mechanisms, and the commonly used excipients, the characterization, and the novel drug delivery systems (microbubbles, microsponges), as well as the preparations used in therapy are discussed in detail.